Literature Review : Efektivitas Project Based Learning dalam Meningkatkan Hasil belajar dan Literasi Sains Siswa Biologi - Amanda Riskina Ramadhani; Meilin Meilin; Adhel Shalsabila; Nasywa Qurrota Aini; Jodion Siburian; Ali Sadikin; Lely Mardiyanti (Universitas Palan, 2026)
Biology learning in Indonesia is still predominantly teacher-centered, limiting students’ opportunities to actively develop critical thinking, creativity, collaboration, and other 21st-century competencies. Students often receive information passively, resulting in low engagement and limited ability to apply concepts in real-life contexts. Therefore, innovative learning models are needed to support more meaningful and student-centered learning. This study aims to review the implementation of Project-Based Learning (PjBL) in Biology education and analyze its contribution to the development of students’ 21st-century skills. The study employed a literature review method by analyzing 20 research articles published between 2022 and 2026. Articles were obtained through Google Scholar searches and selected based on relevance to Biology education, focus on PjBL implementation, and open-access availability. Data collection involved identification, screening, selection, and documentation of related studies, while data analysis used a qualitative descriptive approach. The findings indicate that PjBL effectively improves students’ cognitive achievement, conceptual understanding, scientific literacy, creativity, and critical thinking skills. In addition, PjBL enhances collaboration, communication, problem-solving abilities, learning motivation, and life skills through contextual and authentic project activities. Students become more actively involved in investigating real-world problems, designing solutions, and producing meaningful learning outputs. Furthermore, the integration of STEM approaches, digital media, blended learning, and Culturally Responsive Teaching (CRT) strengthens the effectiveness of PjBL in Biology learning. Overall, PjBL is highly relevant for supporting the Merdeka Curriculum and improving the quality of Biology education in developing 21st-century competencies.